Studies in Hygrocybe s.l. (Hygrocyboideae, Hygrophoraceae) in Brazil: New species of Humidicutis and Neohygrocybe - Simon Cardoso, Juli; Moncalvo, Jean-Marc; Lodge, D. Jean; Margaritescu, Simona; Neves, Maria Alice; S. Oliveira, Jadson J. (Phytotaxa, 2023)
Humidicutis and Neohygrocybe are genera of wax cap mushrooms closely related to Hygrocybe. This is the first study in Humidicutis and Neohygrocybe from Brazil. We describe two new species, H. pindorama and N. fumosa, based on morphology and ITS rDNA data, and propose a new combination, N. ovinoides. Maximum Likelihood and Bayesian analyses were conducted to reconstruct the phylogenetic relationships of the new species and related taxa. The resulting trees suggest that the new species are unique and show significant similarities to existing taxa in their respective genera. We also provide a key to the species of Humidicutis and Neohygrocybe known in the world.